Peningkatan Keterampilan Melalui Program Magang di Divisi Campaign Management & Advertorial Designer (Studi Kasus PT Liputan Enam Dot Com) - Amelia Putri Darmaji; Ajat Sudrajat (STIE AMKOP, 2023)
This article aims to uncover the practies of Campaign Management & Advertorial Designer at Emtek Digital, eith a focus on a case study within KapanLagi Youniverse (KLY). KLY pursues the vision and mission of becoming a leader in online media in indonesia, providing integrated digital solutions to enchance the quality of life in the era of digitalization. The reserch methodology employed is qualitative with a descriptive approach, concentrating on the activities and procedures within the Campaign Management & Advertorial Designer division at KLY. The research findings identify 7 key stages essential for carrying out tasks within the division. This article serves as as a guide and insight for individuals interested in working in the online media industry who share the vision of KLY and Emtek Digital. Keywords : Campaign Management & Advertorial Designer, KapanLagi Youniverse